Are transparency and accountability enough? Open corruption and why it exists - Dahyeon Jeong; Ajay Shenoy; Laura Zimmermann (University of California, Economics Department, 2018)
The global movement against corruption has long assumed its demise lay in transparency and accountability. We test this assumption by measuring whether highly accountable Indian village council presidents favor their own households while making observable allocations of public works jobs. We link millions of public works records to election outcomes. We find that winners of close elections receive 3 times as many days of labor as losers, earning excess wages equaling two-thirds of the median president's salary. Using an original survey of council presidents we find suggestive evidence that corruption is "performance pay" used to attract talented candidates into office.
Keywords: D72; D73; H53; H75; I38; 330